2009
DOI: 10.4137/cmed.s2974
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Medicine: Endocrinology and Diabetes: Abnormality of Serum Lipids are Independently Associated with Increased Serum Calcium Level in the Adult Newfoundland Population

Abstract: Some epidemiological evidence shows a link between abnormality of lipid profiles and variations in serum calcium. However, it is unknown whether this association resulted from confounding factors. The present study was designed to investigate the relationship between serum lipids and calcium. Serum calcium was corrected for albumin. Major confounding factors including age, gender, medications, menopause, parathyroid hormone (PTH) and 25-OH-vitamin D status were controlled in analyses. A total of 1907 adult sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…We also found significantly higher levels of total cholesterol and HDL cholesterol in higher tertiles of serum calcium, as has been previously described in other populations (33)(34)(35)(36). Whether these results could be explained through high parathyroid hormone (PTH) levels (37) cannot be assessed because of lack of information regarding PTH levels in our study.…”
Section: Discussionsupporting
confidence: 68%
“…We also found significantly higher levels of total cholesterol and HDL cholesterol in higher tertiles of serum calcium, as has been previously described in other populations (33)(34)(35)(36). Whether these results could be explained through high parathyroid hormone (PTH) levels (37) cannot be assessed because of lack of information regarding PTH levels in our study.…”
Section: Discussionsupporting
confidence: 68%
“…No studies are available in the literature concerning variations in iCa 2+ levels during different PD stages in dogs. Unlike in humans, where gender-based variations in iCa 2+ levels have been observed [59,60], the distribution of iCa 2+ levels was similar in both genders in our study, with no statistically significant differences observed (p = 0.26). As age increases, iCa 2+ values decrease [61] (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…The proposed mechanisms by which total calcium affects lipid metabolism are that calcium interferes with lipid absorption in the gut since it can bound to fatty acids and bile salts hydrolase. [15] While HDL-c increasing effect of calcium may be through a reduction in the activity of plasma cholesteryl ester transport protein (CETP). [25] We observed a significant association between measured lipoproteins except HDL-c and serum total calcium in OCP users.…”
Section: Discussionmentioning
confidence: 99%
“…This active form of vitamin D regulates serum calcium levels by increasing calcium absorption from diet in the intestine and tubular re-absorption of calcium in the kidney. [15,25] A large Swedish health screening survey reported that changes in calcium metabolism, even within the physiological range, were related to increased blood pressure, impaired glucose tolerance and dyslipidaemia. [44] The increased serum total calcium levels in some subjects on low-dose OCP may be due to increased intestinal absorption, renal absorption, increased skeletal resorption or a combination of these factors since these activities are mediated by parathyroid hormone (PTH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation